PENGGUNAAN MEDIA KARTU KUARTET PADA MATERI KEBERAGAMAN SUKU BANGSA UNTUK MEMOTIVASI BELAJAR SISWA KELAS III MI MA’ARIF NU NURUL ULUM GRESIK (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the extent to which the use of quartet card learning media can increase students' learning motivation in studying the topic of cultural diversity in third-grade students at MI Ma’arif NU Nurul Ulum Gresik. The background of this study is the low learning motivation of students due to the limited variety of media used by teachers in learning. The research method used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation involving 36 third-grade students. The findings of the study reveal that the use of quartet card learning media can encourage a more active and enjoyable learning atmosphere, as well as promote cooperation among students. Students show increased participation, enthusiasm for learning, and the ability to understand the concept of cultural diversity contextually. Factors influencing the effectiveness of this media include the attractive design of the cards, the teacher's creativity in classroom management, and the characteristics of students who enjoy game-based learning activities. Thus, quartet card media can be used as an alternative innovative learning tool that can enhance motivation and learning outcomes of elementary school students, especially in Pancasila Education lessons.